ARTIFICIAL INTELLIGENCE IN EDUCATION - ALIYEVA, Elmira Eyyub; MIRKASIMOVA, Zilola Alisherovna (The Lingua Spectrum, 2025)
Artificial intelligence (AI) has become an integral part of the modern educational system, offering innovative solutions for improving the quality of learning and personalizing the learning process. In this article, we will examine various AI technologies used in education and provide examples of their successful implementation. Modern educational systems utilize a variety of AI technologies, each of which contributes to improving the learning process. Artificial intelligence (AI) is a technology that enables computers to perform tasks that require human intelligence by mimicking functions such as learning, reasoning, and decision making. Simply put, it is the ability of machines to «think” and «learn” by analyzing large amounts of data and finding patterns in it. Examples of its work include speech recognition, text and image generation, and chess playing. Artificial intelligence (AI) is a field of computer science that focuses on creating machines and systems capable of performing tasks that require human intelligence. AI imitates human cognitive functions, such as learning, pattern recognition, decision making, and problem solving. Examples of its applications include natural language processing, computer vision, and expert systems. The need for integrating artificial intelligence into the learning process, as well as the technologies already in use, is identified and analyzed. The potential for using artificial intelligence in personalized learning is presented. Having analyzed the potential applications of artificial intelligence, we conclude that there is a need to utilize and improve neural network and artificial intelligence technologies in education.